Dynamic behavior of a linear induction motor - Creppe, Renato C. [UNESP]; Souza, Carlos R. de [UNESP]; Simone, Gilio A. [UNESP]; Serni, Paulo J A [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1998)
Although conventional rotating machines have been largely used to drive underground transportation systems, linear induction motors are also being considered for future applications owing to their indisputable advantages. A mathematical model for the transient behavior analysis of linear induction motors, when operating with constant r.m.s. currents, is presented in this paper. Operating conditions, like phase short-circuit and input frequency variations and also some design characteristics, such as air-gap and secondary resistivity variations, can be considered by means of this modeling. The basis of the mathematical modeling is presented. Experimental results obtained in the laboratory are compared with the corresponding simulations and discussed in this paper.
Keywords: Electric conductivity; Electric currents; Equivalent circuits; Linear motors; Mathematical models; Natural frequencies; Short circuit currents; Transients; Input frequency variations; Linear induction motors; Induction motors